Pengaruh Bauran Komunikasi Pemasaran Terhadap Ekuitas Merek Produk Adorable Projects - Dewangga, Yudha; Tiorida, Ermina (POLITEKNIK NEGERI BANDUNG, 2015)
Influence society for the survival of a company or micro-enterprises is very important because there is a strong continuity for complementarity. Where the company requires a buyer and society requires equipment such as clothing and the need to want to perform better. And this continuity is a very supportive relationship the company's success in creating marketing communications mix, which also affects the increase in sales of the company itself, especially Adorable Projects which are capable enough to provide convenience - convenience to the public (consumers) in the marketing of their products. And on the ease - the ease that is given Adorable Projects in marketing their products, will Adorable Projects can measure the brand equity is, whether the Community has made their top choice in the selection of the brand, especially in the field of Fashion which incidentally is generally in the city and especially in the city of Cimahi many outlets that offer similar products and with competitive prices. The scale of influence marketing communication mix factor aginst the brand equity in Adorable Projects product is 19.5%. The promotion which has done do by Adorable Projects have the positive influence but still strong and significant against brand equity to choose Adorable Projects product. That thing show by the value of F calculation (ANOVA) still bigger than F table (13,014> 2,004) because only in 13,014 points and have the mistake probability less or more than 10%.